How dictatorships work : power, personalization, and collapse - Geddes, Barbara 1944- (Cambridge University Press, 2018)
“This accessible volume shines a light on how autocracy really works by providing basic facts about how post-World War II dictatorships achieve, retain, and lose power. The authors present an evidence-based portrait of key features of the authoritarian landscape with newly collected data about 200 dictatorial regimes. They examine the central political processes that shape the policy choices of dictatorships and how they compel reaction from policy makers in the rest of the world. Importantly, this book explains how some dictators concentrate great power in their own hands at the expense of other members of the dictatorial elite. Dictators who can monopolize decision making in their countries cause much of the erratic, warlike behavior that disturbs the rest of the world. By providing a picture of the central processes common to dictatorships, this book puts the experience of specific countries in perspective, leading to an informed understanding of events and the likely outcome of foreign responses to autocracies.” (Publisher's description)